Achieving relationship satisfaction: household gender equality and mattering - Karananeethi, Abirami; Prihadi, Kususanto Ditto; Ho, Yi Ming; Shoba, Cynthia; Nesan, Gaayatri; Cahyanti, Ika Yuniar; Surjaningrum, Endang Retno (Intelektual Pustaka Media Utama, 2024)
This study delves into the dynamics of relationship satisfaction (RS) among married couples and its crucial significance for mental health and psychological well-being. Survey data encompassing variables such as the general mattering scale, gender inequality in Household Chores scale, kansas marital conflict scale, and relationship assessment scale were gathered from 128 married individuals aged 18 to 65 in urban areas of Malaysia and Indonesia. Participants furnished demographic information including age, gender, and marriage duration. The study variables were assessed through the scales mentioned earlier. The findings, derived from bootstrap analysis involving 5,000 samples at a 95% confidence interval, revealed that the extent of partners' involvement in household chores significantly predicted their perception of gender equality in domestic responsibilities. This perception, in turn, fostered an elevated sense of mattering, thereby contributing to heightened relationship satisfaction. Importantly, the general mattering scale served as a significant mediator in the relationship between partner's household involvement and relationship satisfaction. In summary, couples benefit from partners engaging in domestic chores, resulting in an enhanced sense of mutual significance, greater relationship satisfaction, and improved mental well-being. Marital conflict frequency and intensity did not emerge as significant factors in this relationship.